Shrinking in bael: A new malady in subtropical region of India - Dwivedi, S K; Singh, Sanjay Kumar; Pandey, Devendra; Poojan, Shiv (Indian Horticulture, 2024)
Bael (Aegle marmelos Correa), a wonder tree, is one of the important lesser utilized fruit crops grown mainly in semi-arid region. Being hardy in nature, it looks immune to insect, pests/or diseases but in reality suffered with various diseases, viz. gummosis, fruit rot, anthracnose, leaf spots and pests like lemon butterfly, leaf miner and termites. Further, physiological disorder also came into picture like fruit cracking, fruit drop and sun scalding. Physiological disorder negatively influenced the fruit texture and a significant yield loss was also reported. For managing them, some simple management tactics that keep away the pests/pathogens andalleviate the non-parasitic disorders, are recommended.